Penggunaan Strategi Relating, Experiencing, Applying, Cooperating, Transferring pada Pembelajaran Bangun Ruang Sisi Lengkung - Munjiyah - (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2015)
REACT is one of strategies applied in math learning, especially on BRSL material. This strategy is expected to enable students to learn and improve their learning achievement. Qualitative research design and classroom action research design were conducted in this research. The findings of this study revealed that the students’ activities while they are in the phase of experiencing are extremely dominant. They were very enthusiastic when they were asked to explore the concept of BRSL through the implementation of REACT strategy.Meanwhile,they did not get actively involved in an intense activity in the phase of transferring. In reference to the research findings, it can be concluded that REACT strategy can evolve response and activities of the ninth grade students of SMP Negeri 1 Yosowilangun.Keywords: REACT, BRSL.